2021
DOI: 10.1186/s13017-021-00375-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection prevention and management in immunocompromised patients: a systematic review of the literature

Abstract: Background Immunocompromised patients are at higher risk of surgical site infection and wound complications. However, optimal management in the perioperative period is not well established. Present systematic review aims to analyse existing strategies and interventions to prevent and manage surgical site infections and other wound complications in immunocompromised patients. Methods A systematic review of the literature was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
0
11
0
2
Order By: Relevance
“…Ovadia et al 35 also found similar infection rates between wound drainage and no drainage groups in a follow-up of 100 patients with postoperative scoliosis. The reasons for these outcomes are as follows: firstly, most new postoperative wound infections may be related to the aseptic operations of clinicians, patients' immune functions and postoperative care by nursing staff, [36][37][38] and cannot be solely attributed to the use of wound drainage; secondly, regardless of infection, as long as toxic substances are drained from the wound, promoting blood circulation and reducing the diffusion distance of oxygen and nutrients, wound healing can be accelerated, thus shortening the healing time. [39][40][41] This study has certain limitations: Firstly, the diseases included in the studies vary, resulting in differences in surgical methods and wound sizes; secondly, the number of studies included is small, which may introduce bias into the meta-analysis results, necessitating further large sample research in the future; third, in addition to evaluating objective indicators such as wound healing time and infection, other assessment criteria should be added to comprehensively evaluate the application value of wound drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Ovadia et al 35 also found similar infection rates between wound drainage and no drainage groups in a follow-up of 100 patients with postoperative scoliosis. The reasons for these outcomes are as follows: firstly, most new postoperative wound infections may be related to the aseptic operations of clinicians, patients' immune functions and postoperative care by nursing staff, [36][37][38] and cannot be solely attributed to the use of wound drainage; secondly, regardless of infection, as long as toxic substances are drained from the wound, promoting blood circulation and reducing the diffusion distance of oxygen and nutrients, wound healing can be accelerated, thus shortening the healing time. [39][40][41] This study has certain limitations: Firstly, the diseases included in the studies vary, resulting in differences in surgical methods and wound sizes; secondly, the number of studies included is small, which may introduce bias into the meta-analysis results, necessitating further large sample research in the future; third, in addition to evaluating objective indicators such as wound healing time and infection, other assessment criteria should be added to comprehensively evaluate the application value of wound drainage.…”
Section: Discussionmentioning
confidence: 99%
“…47 Thus, health services must be able to prepare for well-timed action and mitigation strategies to prevent the catastrophes that have occurred following the outbreak of COVID-19, and to ensure medical intervention and care are available when needed, even in less critical cases. Furthermore, Coccolini and colleagues 48 state that resilient health systems must be built as part of pandemic preparedness, to promptly detect, assess, report, and respond to novel outbreaks. Pandemics cannot be controlled by science alone, with management requiring an integrated approach coordinating science, public outreach, and policy-makers to improve the control of public health emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the risk of a surgical site infection from open surgical fixation is approximately 1.07% in the U.S. in the healthy patient population, and increases with immunocompromised patients. [ 10 , 11 ]. Though minimal, the risk of infection from a minimally invasive injectable compound may be comparable to the risk of infection from open surgical fixation, and should still be taken into consideration.…”
Section: Implications Of the Hypothesismentioning
confidence: 99%